Flourishing consumers from brands: brand well-being's conception, dimensions and scale. Issue 3 (30th October 2020) - Shu, Lifang; Wei, Haiying; Ran, Yaxuan
Abstract : Purpose: The present research aims to construct the brand well-being concept and develop the brand well-being scale. Design/methodology/approach: By interviewing 21 consumers and coding interview text, the authors propose and construct the definition of brand well-being. Using two large sample surveys, the authors develop 11 items for the brand well-being scale. Findings: By interviewing 21 consumers and coding interview text, the authors propose and construct the definition of brand well-being. Using two large sample surveys, the authors develop 11 items for the brand well-being scale. Originality/value: This research combines the branding theory and positive psychology theory, expands the extant understanding of brand value and provides new insights into optimizing a brand strategy.